Low-level viremia in people with HIV in Ethiopia is associated with subsequent lack of viral suppression and attrition from care - Ilili Jemal Abdulahi; Per Björkman; Alemseged Abdissa; Patrik Medstrand; Anton Reepalu; Olof Elvstam (Global Health Action)
Background Low-level viremia during antiretroviral therapy (ART) has been associated with inferior outcomes, but knowledge on the impact of low-level viremia in the current era of dolutegravir-based ART in low-income countries is limited. Objective To investigate whether low-level viremia predicts virologic non-suppression and attrition from care in people with HIV receiving ART in Ethiopia. Methods We included people receiving ART at public health facilities in an urban area in central Ethiopia and categorized persons with ≥1 available viral load 2019–2020 as having either suppression (<150 copies/mL) or low-level viremia (151–1,000 copies/mL); people with >1,000 copies/mL were excluded. We used multivariable logistic regression adjusted for age, sex, ART regimen, type of health facility, and duration of ART to analyze the associations between viremia category and incidence of unsuppressed viral load (>1,000 copies/mL) and attrition from care (death or loss to follow-up) during 3 years of follow-up. Results Among 12,165 participants, the median age was 44 years, 64.2% were female, and 89.1% received tenofovir/lamivudine/dolutegravir. Of the study population, 11,959 (98.3%) had suppression and 206 (1.7%) had low-level viremia. Over 3 years of follow-up, 2.2% of participants with suppression and 11.3% with low-level viremia had unsuppressed viral load. Low-level viremia was associated with both unsuppressed viremia (adjusted odds ratio [aOR], 3.7; 95% confidence interval [CI], 2.2–6.2) and attrition (aOR, 3.4; 95% CI, 1.7–6.6). Conclusion Among Ethiopian people with HIV receiving ART, low-level viremia predicted subsequent virologic non-suppression and attrition from care, supporting current recommendations for heightened attention to low-level viremia in ART recipients.